RETRACTED: Dynamic of Foreign Direct Investment (FDI) Relationship, Macroeconomic Stability and Return of Shares Index in Four Asen Countries - Fisit Suharti; M. Zidny Nafi' Hasbi (el-Jizya : Jurnal Ekonomi Islam, 2021)
Following a rigorous and careful concerns and consideration in the review of the article published in el-Jizya : Jurnal Ekonomi Islam entitled “Dynamic of Foreign Direct Investment (FDI) Relationship, Macroeconomic Stability and Return of Shares Index in Four Asen Countries” Vol 9, No 1, pp. 38-55, Juni 2021, DOI: https://doi.org/10.24090/ej.v9i1.4855. This paper has been found to violate the principles of el-Jizya : Jurnal Ekonomi Islam Publication and has been retracted. The document and its content have been removed from el-Jizya : Jurnal Ekonomi Islam, and reasonable effort should be made to remove all references to this article.